GEC-ESTRO multicenter phase 3-trial: Accelerated partial breast irradiation with interstitial multicatheter brachytherapy versus external beam whole breast irradiation: Early toxicity and patient compliance. Issue 1 (July 2016) - Ott, Oliver J.; Strnad, Vratislav; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Łyczek, Jaroslaw; Guinot, José Luis; Dunst, Jürgen; Miguelez, Cristina Gutierrez; Slampa, Pavel; Allgäuer, Michael; et al.
Abstract: Background and purpose: To compare early side effects and patient compliance of accelerated partial breast irradiation (APBI) with multicatheter brachytherapy to external beam whole breast irradiation (WBI) in a low-risk group of patients with breast cancer. Material and methods: Between April 2004 and July 2009, 1328 patients with UICC stage 0–IIA breast cancer were randomized to receive WBI with 50 Gy and a boost of 10 Gy or APBI with either 32.0 Gy/8 fractions, or 30.1 Gy/7 fractions (HDR-brachytherapy), or 50 Gy/0.60–0.80 Gy per pulse (PDR-brachytherapy). This report focuses on early side-effects and patient compliance observed in 1186 analyzable patients. ClinicalTrials.gov identifier: NCT00402519. Results: Patient compliance was excellent in both arms. Both WBI and APBI were well tolerated with moderate early side-effects. No grade 4 toxicity had been observed. Grade 3 side effects were exclusively seen for early skin toxicity (radiation dermatitis) with 7% vs. 0.2% ( p < 0.0001), and breast infection with 0% vs. 0.2% ( p = n.s.) for patients treated with WBI and APBI. The incidence of grades 1–2 early side effects for WBI and APBI was 86% vs. 21% ( p < 0.0001) for skin toxicity, 2% vs. 20% ( p < 0.0001) for mild hematoma, and 2% vs. 5% ( p = 0.01) for mild breast infection rates, respectively. No differences had been found regarding grades 1–2 early breast pain (26% vs. 29%, p = 0.23). Conclusions: APBI with interstitial multicatheter brachytherapy was tolerated very well and dramatically reduced early skin toxicity in comparison to standard WBI.